Anwar Sadat - Aufderheide, Patricia (New York : Chelsea House, 1985)
A biography of the Egyptian President who worked for peace in the Middle East.
Includes index.
Bibliography: p. 108.
Wilson's Junior High School.
8.8
5-8
7-9
Keywords: Sadat, Anwar, -- 1918- -- Juvenile literature; Sadat, Anwar, -- 1918-; Sadat, Anwar, -- 1918-1981.; Presidents -- Egypt -- Biography; Presidents -- Egypt; Presidents -- Egypt -- Biography